Body size of male youth soccer players: 1978-2015 - Malina, R. M.; Figueiredo, A. J.; Coelho e Silva, M. J. (Sports Medicine, 2017)
Studies of the body size and proportions of athletes have a long history. Comparisons of athletes within specific sports across time, though not extensive, indicate both positive and negative trends. Objective: To evaluate secular variation in heights and weights of male youth soccer players reported in studies between 1978 and 2015. Methods: Reported mean ages, heights, and weights of male soccer players 9-18 years of age were extracted from the literature and grouped into two intervals: 1978-99 and 2000-15. A third-order polynomial was fitted to the mean heights and weights across the age range for each interval, while the Preece-Baines model 1 was fitted to the grand means of mean heights and mean weights within each chronological year to estimate ages at peak height velocity and peak weight velocity for each time interval. Results: Third-order polynomials applied to all data points and estimates based on the Preece-Baines model applied to grand means for each age group provided similar fits. Both indicated secular changes in body size between the two intervals. Secular increases in height and weight between 1978-99 and 2000-15 were especially apparent between 13 and 16 years of age, but estimated ages at peak height velocity (13.01 and 12.91 years) and peak weight velocity (13.86 and 13.77 years) did not differ between the time intervals. Conclusion: Although the body size of youth soccer players increased between 1978-99 and 2000-15, estimated ages at peak height velocity and peak weight velocity did not change. The increase in height and weight likely reflected improved health and nutritional conditions, in addition to the selectivity of soccer reflected in systematic selection and retention of players advanced in maturity status, and exclusion of late maturing players beginning at about 12-13 years of age. Enhanced training programs aimed at the development of strength and power are probably an additional factor contributing to secular increases in body weight.